Cerebral Venous Sinus Thrombosis in a Patient with Ulcerative Colitis Flare - L. M. Conners; R. Ahad; P. H. Janda; Z. Mudasir (Case Reports in Neurological Medicine)
Inflammatory bowel disease is characterized by a chronic inflammatory state and is therefore associated with abnormalities in coagulation and a hypercoagulable state. Cerebral venous sinus thrombosis is a rare complication of inflammatory bowel disease yet contributes significant morbidity and mortality to those affected. Early diagnosis is critical, as a delay in diagnosis portends a worse prognosis. This paper seeks to highlight the increased risk of venous sinus thrombosis in patients with inflammatory bowel disease. We start by discussing the case of a seventeen-year-old female who presented with ulcerative colitis flare and developed new-onset seizures, found to be caused by a large venous sinus thrombosis.